2019
DOI: 10.1111/jfd.13051
|View full text |Cite
|
Sign up to set email alerts
|

Renibacterium salmoninarum iron‐acquisition mechanisms and ASK cell line infection: Virulence and immune response

Abstract: Renibacterium salmoninarum is the aetiological agent of bacterial kidney disease (BKD) in salmonid farms. This pathogen possesses at least three iron‐acquisition mechanisms, but the link between these mechanisms and virulence is unclear. Therefore, this study used RT‐qPCR to assess the effects of normal and iron‐limited conditions on iron‐uptake genes controlled by IdeR and related to iron acquisition in Chilean R. salmoninarum strain H‐2 and the type strain DSM20767T. Further evaluated was the in vitro immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…This strain was isolated from fish with clinical signs of BKD in southern Chile. Previous studies showed that strain H-2 has high siderophore production, which can result in high virulence potential (14,32,33). The strain identification was confirmed as R. salmoninarum with nested PCR, as described by Chase and Pascho (34), and culture purity was confirmed by Gram-staining, cell morphology and colony morphology (33).…”
Section: R Salmoninarum Strain and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This strain was isolated from fish with clinical signs of BKD in southern Chile. Previous studies showed that strain H-2 has high siderophore production, which can result in high virulence potential (14,32,33). The strain identification was confirmed as R. salmoninarum with nested PCR, as described by Chase and Pascho (34), and culture purity was confirmed by Gram-staining, cell morphology and colony morphology (33).…”
Section: R Salmoninarum Strain and Culturementioning
confidence: 99%
“…An enhanced understanding of the Atlantic salmon response to R. salmoninarum can aid in the development of preventive management tools for BKD (e.g., vaccines and therapeutic diets). Previous in vivo and in vitro studies examined gene expression responses to R. salmoninarum in rainbow trout (11) and Chinook salmon (O. tshawytscha) (12) kidney as well as rainbow trout macrophages (13) and Atlantic Salmon Kidney (ASK) cell line (14). A genomics-based study used Suppression Subtractive Hybridisation (SSH) to identify BKD-responsive genes in Chinook salmon (15).…”
Section: Introductionmentioning
confidence: 99%
“…Grayson et al [ 100 ] investigated iron acquisition in R. salmoninarum and have reported that non-hydrophobic strains were not able to grow properly under iron-restricted conditions compared with hydrophobic strains. Additionally, two iron acquisition systems (siderophores and haeme) have been described by Bethke et al [ 101 ]. Recently, Bethke et al [ 101 ] investigated the expression of bacterial genes and host immune genes during in vitro infection of a cell line (Atlantic salmon kidney cells) and culture under iron-limited conditions.…”
Section: Virulence Mechanismsmentioning
confidence: 99%
“…Additionally, two iron acquisition systems (siderophores and haeme) have been described by Bethke et al [ 101 ]. Recently, Bethke et al [ 101 ] investigated the expression of bacterial genes and host immune genes during in vitro infection of a cell line (Atlantic salmon kidney cells) and culture under iron-limited conditions. These authors reported that several bacterial genes such as HmuTUV cluster, the siderophore transporters FecB and FecD, the siderophore esterase Est.1 and Est.2 and the ferrous transporter FTR-1 were overexpressed under iron limited conditions, suggesting that these genes play a role in iron acquisition.…”
Section: Virulence Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation